Characterization of biochemical traits of dog rose (Rosa canina L.) ecotypes in the central part of Iran. Issue 14 (18th July 2018) - Javanmard, Milad; Asadi-Gharneh, Hossein Ali; Nikneshan, Pejman
Abstract: Dog rose ( Rosa canina L.) is a wild native species in Iran, with a significant genetic diversity. This plant serves as a rich source of vitamin C, anthocyanins, phenolic contents and carotenoids. Rose hips have been used in several food products, as well as perfumery and cosmetics industries. In this research, we investigate biochemical characteristics of five dog rose ecotypes (Kopehjamshid, Zarneh, Miyankish, Aghcheh and Sadeghiyeh), that were collected from the central part of Iran (Isfahan province). Amounts of vitamin C, total carotenoids, total phenolic contents, total anthocyanins, macro and micro minerals were measured. Seed oil are extracted by soxhlet method and analysed by gas chromatography. The macro and micro minerals levels in the fruit vary significantly among these regions. The results of this study demonstrate that dog rose have great diversity and can be used in breeding programmes in order to increase nutrient values as a food resource additive. Abstract :